(untitled) (Stato, Chiese e pluralismo confessionale, 2012)
Contributo sottoposto a valutazioni SOMMARIO: 1. Premessa - 2. Il fund raising: inquadramento concettuale - 3. (segue) Strategie, strumenti e tecniche di fund raising - 4. Il fund raising come fattore di potenziale sviluppo delle organizzazioni non profit - 5. Enti religiosi e fund raising: un binomio che necessita di essere consolidato (e potenziato) - 6. Peculiarità dell’azione di fund raising degli enti religiosi - 7. Fund raising e aspetti economici e gestionali degli enti religiosi - 8. Considerazioni conclusive. Abstract: Religious organizations and fundraising: a possible combination (indeed necessary) Fund-raising activities represent the principal livelihood and sources of growth and development for non-profit organisations. Fund-raising is, also, an increasingly important part of religious organizations life. Almost each of them engages in some kind of fund-raising activity, with the purpose of generating income to sustain the organization’s programs and activities. The present study analyzes the relationship between religious organizations and fund-raising activities: a correlation that always existed, but now calls for consolidation and improvement in order to allow religious organizations to achieve economic sustainability. Therefore, religious organizations should develop competency and capacity to design and implement fund-raising activities, through appropriate policies, tools and methodologies. In this perspective, the author examines all the facets of fund-raising activities related to the religious organizations sector and, more in general, the possible applications of business administration principles to the management of religious bodies (so-called “church management”). Parole chiave: enti religiosi; fund raising; sostenibilità economica; management